International criminal tribunal for the former Yugoslavia (ICTY), the forensic pathologist and ethics - de la Grandmaison Geoffroy Lorin (Temida)
Forensic pathologists involved in the ICTY missions could be subjected to ethical tensions. In order to study the nature of such tensions, review of the literature and analysis of forensic material available from the trial transcripts relative to Srebrenica massacre were carried out. Forensic evidence used in ICTY trials is weakened by many factors, including especially the difficulties in the interpretation of the autopsy findings and the possibility of a biased selection of exhumations by the Office of the Prosecutor. Although discrepancies exist between forensic evidence and facts established by ICTY judgments about Srebrenica events, genocide charge was not challenged by ICTY, conflicting with the idea that reliably established facts are the foundation of legal analysis. The degree of ethical conflicts in forensic pathologist’s community depends on their level of knowledge respectively about the fundamental principles of the law subverted by ICTY and the political implications of international justice. Ethical guidelines are needed to ease such ethical tensions.